2016
DOI: 10.1080/01621424.2016.1175991
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in home health service providers among Medicare beneficiaries with stroke

Abstract: This study examined the intensity of home health services, as defined by the number of visits and service delivery by rehabilitation specialists, among Medicare beneficiaries with stroke. A cross-sectional secondary data analysis was conducted using 2009 home health claims data obtained from the Centers for Medicare and Medicaid Services' Research Data Assistance Center. There were no significant rural-urban differences in the number of home health visits. Rural beneficiaries were significantly less likely tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Stroke recovery can be a long and complex process, involving multiple domains of therapy (e.g., physical, occupational, communication, and cognitive) and occurs in inpatient rehabilitation facilities, skilled nursing facilities, and outpatient rehabilitation facilities. Benefits of stroke outpatient rehab have been determined to improve patient functional status, survival, cardiovascular risk profiles, and quality of life and reduce risks for recurrent strokes and psychological or stress disorders ( 3 , 4 , 8 , 9 ). Generally, stroke outpatient rehab participation is underutilized ( 3 , 8 ), which this study found to be true for all subgroups and states included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stroke recovery can be a long and complex process, involving multiple domains of therapy (e.g., physical, occupational, communication, and cognitive) and occurs in inpatient rehabilitation facilities, skilled nursing facilities, and outpatient rehabilitation facilities. Benefits of stroke outpatient rehab have been determined to improve patient functional status, survival, cardiovascular risk profiles, and quality of life and reduce risks for recurrent strokes and psychological or stress disorders ( 3 , 4 , 8 , 9 ). Generally, stroke outpatient rehab participation is underutilized ( 3 , 8 ), which this study found to be true for all subgroups and states included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of stroke outpatient rehab have been determined to improve patient functional status, survival, cardiovascular risk profiles, and quality of life and reduce risks for recurrent strokes and psychological or stress disorders ( 3 , 4 , 8 , 9 ). Generally, stroke outpatient rehab participation is underutilized ( 3 , 8 ), which this study found to be true for all subgroups and states included in the analysis. No subgroup had outpatient rehab use rates >40%, and no state had use rates >50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Определены преимущества амбулаторного реабилитационного лече-ния, направленного на улучшение функционального ста-туса пациента, профилей риска сердечно-сосудистых заболеваний и качества жизни, повышение выживаемо-сти, а также на снижение риска повторных инсультов и психологических или стрессовых расстройств [14][15][16][17].…”
unclassified